Inhibition of Protein Aggregation and Endoplasmic Reticulum Stress as a Targeted Therapy for α-Synucleinopathy - Natalia Siwecka; Kamil Saramowicz; Grzegorz Galita; Wioletta Rozpędek-Kamińska; Ireneusz Majsterek (MDPI AG, 2023)
α-synuclein (α-syn) is an intrinsically disordered protein abundant in the central nervous system. Physiologically, the protein regulates vesicle trafficking and neurotransmitter release in the presynaptic terminals. Pathologies related to misfolding and aggregation of α-syn are referred to as α-synucleinopathies, and they constitute a frequent cause of neurodegeneration. The most common α-synucleinopathy, Parkinson's disease (PD), is caused by abnormal accumulation of α-syn in the dopaminergic neurons of the midbrain. This results in protein overload, activation of endoplasmic reticulum (ER) stress, and, ultimately, neural cell apoptosis and neurodegeneration. To date, the available treatment options for PD are only symptomatic and rely on dopamine replacement therapy or palliative surgery. As the prevalence of PD has skyrocketed in recent years, there is a pending issue for development of new disease-modifying strategies. These include anti-aggregative agents that target α-syn directly (gene therapy, small molecules and immunization), indirectly (modulators of ER stress, oxidative stress and clearance pathways) or combine both actions (natural compounds). Herein, we provide an overview on the characteristic features of the structure and pathogenic mechanisms of α-syn that could be targeted with novel molecular-based therapies.